Recent achievements in synthesis of anthracene scaffolds catalyzed transition metals - Fadhil Faez Sead; Fadhil Faez Sead; Fadhil Faez Sead; Vicky Jain; R. Roopashree; Aditya Kashyap; Suman Saini; Girish Chandra Sharma; Pushpa Negi Bhakuni; Pushpa Negi Bhakuni; Mosstafa Kazemi; Ramin Javahershenas (Frontiers in Chemistry)
In the last 10 years, the synthesis of anthracene scaffolds has attracted considerable interest because of their distinctive electronic characteristics and various uses in organic electronics, photovoltaics, and therapeutics. Anthracene, a polycyclic aromatic hydrocarbon, is valued for its lightweight, stability, and electron transport capabilities, making it a key building block in advanced materials. Traditional synthesis methods often face challenges such as low selectivity and harsh conditions. However, recent advancements in transition metal-catalyzed reactions have transformed the field, offering more efficient and versatile approaches. This review examines methodologies utilizing transition metal catalysts like palladium, zinc, indium, cobalt, gold, iridium, rhodium and ruthenium, which have enabled novel synthetic pathways and selective formation of substituted anthracenes through cross-coupling reactions. The function of ligands, including phosphines and N-heterocyclic carbenes, in improving reaction efficiency and selectivity is also examined. The shift towards greener methodologies is noted, with a focus on minimizing waste and reducing toxic reagents. The shift towards greener methodologies is noted, with a focus on minimizing waste and reducing toxic reagents. Several case studies demonstrate the successful application of these techniques, highlighting the structural diversity and functional potential of anthracene derivatives in various applications.